Morphological studies on the head and mouth parts of Leucinodes orbonalis Guenée. Part II - The Imago (Lepidoptera: Pyraustidae). - Srivastava, B. P.; Yadava, C. P. (Contributions to Entomology = Beiträge zur Entomologie, 1969)
A complete description of the head sclerites and the mouth parts is given. It has been established that like the larval head also the clypeus of the adult is bounded dorsally and laterally by the median and the lateral arms of the epistomal suture. The median part of the epistomal suture extends between the two antennal sockets and each of ist lateral arms between the antennal socket and the anterior tentoral invagination of its side. The ventral limit of the frons is formed by the median part of the epistomal suture while ist dorsal end is unlimited. The proboscis of Leucinodes orbonalis is peculiar in so far as the chitinous bands are confined to the inner wall, while the outer wall is formed by a uniformly chitinized membrane without separate bands. Besides the lacinia, regarded as absent in Lepidoptera except the Micropterygidae, is distinguistable in this Pyraustid which thus presents an intermediate stage in the incorporation of the lacinia with the base of the galea.